2021
DOI: 10.3390/ma14237151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Moisture Sensitivity and Damage Evolution of Porous Asphalt Mixtures

Abstract: Porous asphalt (PA) mixtures are designed with a high air void (AV) (i.e., 18~22%) content allowing rainwater to infiltrate into their internal structures. Therefore, PA mixtures are more sensitive to moisture damage than traditional densely graded asphalt mixtures. However, the moisture damage evolution of PA mixtures is still unclear. The objective of this study was to investigate the moisture damage evolution and durability damage evolution of PA mixtures. The indirect tensile test (ITT), ITT fatigue test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In carrying out such a task, it is very important to be aware of specific issues relevant to this type of pavement, including durability and functionality. For example, a study by Hu et al [33] experimentally investigated the moisture sensitivity and damage evolution of porous asphalt mixtures, and their main finding was that, under long-term moisture damage, the moisture sensitivity of porous asphalt mixtures is a concern. They also found that tensile strength and resilience modulus decreased with the increasing loading cycles, and in order to extend the service life of porous asphalt mixtures, maintenance is needed when the decrement of these properties exceeds 60%.…”
Section: Pavement Adaptation In More Robust Materials and MIX Designmentioning
confidence: 99%
“…In carrying out such a task, it is very important to be aware of specific issues relevant to this type of pavement, including durability and functionality. For example, a study by Hu et al [33] experimentally investigated the moisture sensitivity and damage evolution of porous asphalt mixtures, and their main finding was that, under long-term moisture damage, the moisture sensitivity of porous asphalt mixtures is a concern. They also found that tensile strength and resilience modulus decreased with the increasing loading cycles, and in order to extend the service life of porous asphalt mixtures, maintenance is needed when the decrement of these properties exceeds 60%.…”
Section: Pavement Adaptation In More Robust Materials and MIX Designmentioning
confidence: 99%
“…Furthermore, the water will also weaken the adhesion of the pavement layer with the bedding layer and the base layer, weakening the load transfer characteristics of the entire road base pavement system, thus leading to stripping, loosening, holes, potholes, and other diseases. This process is known as asphalt pavement moisture damage [ 2 , 3 ]. Some of the factors that result in the stripping of asphalt mixtures are the material characteristics [ 4 ], mixture voids and connectivity [ 5 ], and hydraulic washout [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt mixtures are granular materials, and their mechanical strength is generally considered to depend on the friction and embedding forces between the aggregate particles, the cohesion of the asphalt binder, and the bond between the asphalt and the aggregate [1]. Erosion due to water can damage the interface between asphalt and aggregate, reducing the adhesion of the asphalt bond [2][3][4][5], resulting in spalling and loosening and reducing the life of the asphalt pavement [6,7].…”
Section: Introductionmentioning
confidence: 99%